2017
DOI: 10.1364/ol.43.000022
|View full text |Cite
|
Sign up to set email alerts
|

Kilohertz binary phase modulator for pulsed laser sources using a digital micromirror device

Abstract: The controlled modulation of an optical wavefront is required for aberration correction, digital phase conjugation or patterned photostimulation. For most of these applications it is desirable to control the wavefront modulation at the highest rates possible. The digital micromirror device (DMD) presents a cost-effective solution to achieve high-speed modulation and often exceeds the speed of the more conventional liquid crystal spatial light modulator, but is inherently an amplitude modulator. Furthermore, sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Hence, the nanostructured biopolymer matrix here developed allows sub-millisecond all-optical switching to be achieved. This is relevant for various spectroscopic, imaging and manufacturing applications, where either intensity or phase modulation of light beams is required 60,64…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the nanostructured biopolymer matrix here developed allows sub-millisecond all-optical switching to be achieved. This is relevant for various spectroscopic, imaging and manufacturing applications, where either intensity or phase modulation of light beams is required 60,64…”
Section: Resultsmentioning
confidence: 99%
“…Research on new spectroscopy systems taking advantage of DMD's capabilities is emerging fast in academia in recent years. 59 Wagner et al¯rst reported a cost-e±cient solution to produce a DMD-based optical spectrometer that only uses a sensitivity optimized photomultiplier tube (PMT). 60 In their design, the DMD was adopted as a selector located at the image point of a spectrum created by a concave grating to manage the speci¯c wavelength components of the incident light.…”
Section: Application Of Dmd In Spectrometersmentioning
confidence: 99%
“…In volumetric holographic data storage, eigenmode and angular multiplexing techniques have been applied to increase storage density [25], and solidstate eigenmode multiplexing by phase-only SLM has been achieved [26]. Additionally, a DMD-based phase-only spatial modulation technique has been previously demonstrated [27]. The phase-amplitude modulation of the ASLM offers the potential for a near-solid-state, single-chip-driven holographic data storage system with spatial and angular multiplexing capabilities for higher storage densities.…”
Section: Diffraction Efficiency Of the Programmable Dmd Blazed Gratingmentioning
confidence: 99%